Fostering collaboration: a controlled pilot study of interprofessional education for medical and pharmacy students - Maike Petersen; Sabine Gehrke-Beck; Nicole Zimmermann; Amrei-Pauline Konrad; Ronja Behrend; Harm Peters; Martin Schulz; Charlotte Kloft; Wolfram J. Herrmann (BMC Medical Education)
Abstract Background An increasingly ageing population and the resulting multimorbidity is a growing challenge for healthcare systems. A solution to tackle this problem is interprofessional collaboration. Interprofessional education, as an early meeting point, could foster a future successful interprofessional collaboration. So, the aim of our pilot study was to assess whether the “interprofessional collaboration between medical and pharmacy students to improve medication safety in polypharmacy” (PILLE) project changed the perception of medical and pharmacy students towards interprofessional collaboration. Methods PILLE consisted of three parts: (1) A mandatory 90-minutes interprofessional seminar; (2) A voluntary 120-minutes practical training; (3) A voluntary half-day interprofessional tandem work shadowing at a General Practitioner’s (GP) office. We used a controlled study design. Medical and pharmacy students from the intervention group attended the seminar (1). Medical students of the control group attended an interactive 90-minutes monoprofessional seminar only. Working together on cases was the similarity of both seminars. The students from the intervention group could attend (2) and (3). The outcome of interest was the change in students’ perception towards interprofessional collaboration after participating in PILLE, using pre- and post-questionnaires with the validated German version of Student Perceptions of Physician-Pharmacist Interprofessional Clinical Education (SPICE-2D) instrument. Descriptive and statistical evaluation was conducted. To assess if there is a significant pre-post-difference in the SPICE-2D overall score within the individual groups, paired t-tests were executed. To investigate if there is a significant change in SPICE-2D overall score difference between the medical students control and intervention group, an unpaired t-test was performed. Results In total, 436 students participated: 96 medical students and 116 pharmacy students in the intervention group, and 224 medical students in the control group. The participating students from both professions already had a pronounced positive perception at baseline. All pre-post-mean-differences within the individual groups and between the medical students control and intervention group were not statistically significant. Conclusion Participating medical and pharmacy students already had a positive perception at baseline. A one-time and short-term mandatory seminar of 90-minutes seems not to be sufficient to measure a change in perception. Future interprofessional education projects should focus on frequent meeting points between students.